The influence of parental attention, facilities, infrastructure, and learning motivation on motor skills of students - Muhammad Fitra Bimafasha; Sri Gusti Handayani; Tjung Haw Sin; Yuni Astuti (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study aims to determine the direct and indirect effects of parental attention, facilities and infrastructure, and learning motivation on motor skills among students at SD Negeri 2 Bengkulu Selatan. The research employed a quantitative approach with a path analysis method. The population comprised all students of SD Negeri 2 Bengkulu Selatan, with a sample of 25 students selected through total sampling. Data were collected using validated questionnaires and analyzed using SPSS version 30.The results indicated that (1) parental attention had a significant direct effect on motor skills (ρyx1 = 0.395; Sig. = 0.044 < 0.05); (2) facilities and infrastructure had no significant direct effect on motor skills (ρyx2 = 0.064; Sig. = 0.742 > 0.05); (3) learning motivation had a significant direct effect on motor skills (ρyx3 = 0.400; Sig. = 0.034 < 0.05). Moreover, the variables of parental attention, facilities and infrastructure, and learning motivation simultaneously contributed 40.3% to motor skills development. It can be concluded that parental attention and learning motivation play dominant roles in enhancing students’ motor skills, whereas the availability of facilities and infrastructure serves a more supportive, indirect function.